2022
DOI: 10.1002/pat.5894
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesis of calcium pimelate as a highly dispersed β‐nucleating agent for improving the crystallization behavior and mechanical properties of isotactic polypropylene

Abstract: The reaction precursors pimelic acid (Pi) and calcium stearate (CaSt) were added in situ during extrusion of isotactic polypropylene (iPP) to generate self‐dispersed calcium pimelate (CaPi[IS]). The results reveal that the nucleating agents (NAs) synthesized in situ obviously affected the nucleation effect in iPP. The crystallization, mechanical properties and melting behavior of nucleated iPP were investigated. The crystallization temperature (Tc) of iPP modified with CaPi(IS) increased by 4–5°C when compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…Polypropylene random copolymer (PPR) is one of the most important derivatives from isotactic polypropylene (iPP) and is widely used in pipelines, automobile parts, and various other industrial applications . As a crystallizable polymer, PPR exhibits two main crystalline modifications from the crystallization of long stereoregular propylene−propylene−propylene (PPP) sequence, monoclinic α-form and triclinic β-form crystals. The α-PP crystals display low deformability due to a cross-hatched texture comprising interlocked parent and daughter lamellae, while in contrast, the metastable β-PP crystals are ductile with twisted parent lamellae. In addition to the crystal structures, the random copolymerization of propylene monomer with ethylene assembles into locally disordered ethylene−propylene (EP) segments, aggregating into spherical EP rubbery phases. It is reported that EP rubbery phases have a low glass transition temperature of ∼−50 °C and are capable of dissipating crack tip energy by increasing crack propagation distance, thus benefiting for toughening. The collaboration from ductile β-crystals and high deformability of EP rubbery phase qualifies a high application value of PPR, which is currently the research focus for toughening.…”
Section: Introductionmentioning
confidence: 99%
“…Polypropylene random copolymer (PPR) is one of the most important derivatives from isotactic polypropylene (iPP) and is widely used in pipelines, automobile parts, and various other industrial applications . As a crystallizable polymer, PPR exhibits two main crystalline modifications from the crystallization of long stereoregular propylene−propylene−propylene (PPP) sequence, monoclinic α-form and triclinic β-form crystals. The α-PP crystals display low deformability due to a cross-hatched texture comprising interlocked parent and daughter lamellae, while in contrast, the metastable β-PP crystals are ductile with twisted parent lamellae. In addition to the crystal structures, the random copolymerization of propylene monomer with ethylene assembles into locally disordered ethylene−propylene (EP) segments, aggregating into spherical EP rubbery phases. It is reported that EP rubbery phases have a low glass transition temperature of ∼−50 °C and are capable of dissipating crack tip energy by increasing crack propagation distance, thus benefiting for toughening. The collaboration from ductile β-crystals and high deformability of EP rubbery phase qualifies a high application value of PPR, which is currently the research focus for toughening.…”
Section: Introductionmentioning
confidence: 99%